1984
DOI: 10.1029/jc089ic05p08197
|View full text |Cite
|
Sign up to set email alerts
|

The effect of particle size on the light attenuation coefficient of natural suspensions

Abstract: Laboratory calibration of a beam transmissometer by using natural sedimentary particles fractionated into seven size classes demonstrates that slopes of light attenuation vs. particle mass concentration regressions systematically vary with the size distributions of the particles. Suspensions with a mean particle size of 8.5 μm attenuate 660‐nm light 15 times more efficiently than suspensions of similar particles with a mean diameter of 48 μm. Theoretical calculations of attenuation, based on scattering by sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
144
0
3

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(154 citation statements)
references
References 26 publications
7
144
0
3
Order By: Relevance
“…Suspended particle concentrations (CL) were determined by the same procedure as for river samples. Since suspended matter in natural water consists of specific mixtures of different sizes and types of particles, calibration is required to determine CL based on in situ light transmission [Baker and Lavelle, 1984;Gordon et al, 1984;Hofmann and Dominik, 1995]. Light attenuation at 660 nm can unambiguously be related to particle concentrations assuming that the particle mixture is homogeneous and the attenuation by the water is constant [Boss et al, 2001].…”
Section: Particle Distributions In Downstream Lake Brienzmentioning
confidence: 99%
“…Suspended particle concentrations (CL) were determined by the same procedure as for river samples. Since suspended matter in natural water consists of specific mixtures of different sizes and types of particles, calibration is required to determine CL based on in situ light transmission [Baker and Lavelle, 1984;Gordon et al, 1984;Hofmann and Dominik, 1995]. Light attenuation at 660 nm can unambiguously be related to particle concentrations assuming that the particle mixture is homogeneous and the attenuation by the water is constant [Boss et al, 2001].…”
Section: Particle Distributions In Downstream Lake Brienzmentioning
confidence: 99%
“…In addition to increased particle loading, 197 bottom scavenging may also be affected by a change in particle composition. This section is also 198 well suited to test the hypotheses that 230 Th and 231 by transmissometer from CTD casts, which is, to first order, linearly related to particle 205 concentration (Bishop, 1986;Gardner et al, 1985), although the sensitivity of Cp to particle 206 concentration is known to vary with particle size and composition (Baker and Lavelle, 1984;207 Richardson, 1987). …”
mentioning
confidence: 99%
“…The error bars are ± 1 standard deviation of particle diameter or calibration Baker and Lavelle's experimental point at 106 ym where the mean diameter was estimated as the midpoint of the size range. The differences for natural sediment are probably due to differences in particle shape and the roughness of the natural sediment samples as discussed by Baker and Lavelle (1984).…”
Section: Single Particle Classesmentioning
confidence: 99%
“…(Sternberg and Creager, 1965;Drake and Cacchione, 1985;and Williams, 1985). Our laboratory calibrations of some of these sensors (presented in this paper) and those of Baker and Lavelle (1984) have shown that the proportionality constant between light attenuation A2-1 coefficient (c ) and suspended matter concentration (SMC) is a function of particle size. Therefore, a companion time series of suspended particle size is necessary to estimate SMC from these light transmission measurements.…”
Section: Al-19mentioning
confidence: 99%
See 1 more Smart Citation